Receptor antagonism/agonism can be uncoupled from pharmacoperone activity. (15th October 2016) - Janovick, Jo Ann; Spicer, Timothy P.; Smith, Emery; Bannister, Thomas D.; Kenakin, Terry; Scampavia, Louis; Conn, P. Michael
Abstract: Pharmacoperones rescue misrouted mutants of the vasopressin receptor type 2 (V2R) and enable them to traffic to the correct biological locus where they function. Previously, a library of nearly 645, 000 structures was interrogated with a high throughput screen; pharmacoperones were identified for V2R mutants with a view toward correcting the underlying mutational defects in nephrogenic diabetes insipidus. In the present study, an orthologous assay was used to evaluate hits from the earlier study. We found no consistent relation between antagonism or agonism and pharmacoperone activity. Active pharmacoperones were identified which had minimal antagonistic activity. This increases the therapeutic reach of these drugs, since virtually all pharmacoperone drugs reported to date were selected from peptidomimetic antagonists. Such mixed-activity drugs have a complex pharmacology limiting their therapeutic utility and requiring their removal prior to stimulation of the receptor with agonist. Highlights: First study to identify small molecules that impact receptor trafficking without competing for native ligand binding site. Antagonist and agonist activities are uncoupled from pharmacoperone activity, enhancing the drugs therapeutic potential. The data may suggest that some pharmacoperones can rescue proteins acting by allosteric interactions. Pharmacoperone drugs can be identified that are not agonists or antagonists.